Analysis of Macro Nutrient on Rono Fish (Xenopoecilus oophorus) Freshwater - Delviana Melego; Mery Napitupulu; Daud K. Walanda (Universitas Tadulako, 2019)
Fish are assumed to have high nutritional value with mineral content, vitamins, fats, and proteins containing essential amino acids that are needed for growth and human intelligence. One type of them is rono fish (Xenopoecilus oophorus) freshwater which is an endemic fish that comes from lake Poso, Central Sulawesi and still found in traditional markets of Tentena city, but the local community is less interested in this type of fish and the lack of literature that informs about the nutritional content of rono fish. The research aims to determine the macronutrient content in rono fish. The nutrient content analyzed in fish was on carbohydrates, proteins, and fats by using the anthrone sulfate method for carbohydrate analysis, Kjeldahl method for protein, and for fat analysis using the soxhlet method. The results of the analysis obtained that macronutrient in freshwater rono fish was followed carbohydrate was 9.26%, the protein was 37.79% and fat was 11.92%.